Relationship between parents and children and academic performance of college Students Maria Parado de Bellido. - Anco-Torres, German D. (2019)
Facing the lack of knowledge about the importance of communication between parents and children, and this means being today a very important for personal development of human and aware that this issue needs urgent treatment in the present context be tool proceeded to study to determine the relationship between these variables. Communication plays an important role; is a two-way bridge connecting the feelings of parents and children. However, as is obvious when this communication is impaired, there are negative consequences that seriously jeopardize the formation of adolescents. In this research it is to show the consequences that the communication problems between parents and children generated in academic performance. The above considerations led to the implementation of the record of interview with the authorities and teachers and the questionnaire to students enrolled in the sixth grade of primary education of School Maria Parado de Bellido of the town of Cerro de Pasco, in order to know the level of relationship between fathers and daughters and academic performance of the students. The results achieved from the implementation of the interview and questionnaire for determining that most students do not have good communication with their parents and therefore have a low level of academic achievement. It is concluded that urgent need to improve communication with parents and raising academic performance.